Correlates of obesity indices and cardiovascular disease risk factors among Trinidadian nurses. (2020) - Donkor, Noble; Farrell, Kathleen; Ocho, Oscar; Sheppard, Claudine; Caesar, Lu Ann; Andrews, Lydia; Modeste, Sylvia; Otieno, Peter; Acquah, Sandra
Abstract: Background: The incidence of many chronic diseases is high among people who are obese. Therefore, identifying the association of obesity indices and cardiovascular risk factors among nurses can be useful in the advancement of public health policy and ensuring quality of life for frontline healthcare workers. Objective: The present study examines the association of obesity indices and cardiovascular disease risk factors among nurses in Trinidad and Tobago. Methods: This cross-sectional study was conducted among nurses attending the Excellence in Nursing Practice Workshop in Port of Spain, Trinidad and Tobago in June 2017. Trained nurses collected data about age, body mass index, waist circumference, conicity index, systolic and diastolic blood pressure and fasting blood glucose. The associations between obesity indices and cardiovascular risk factors were explored with Pearson's correlation coefficient and One-way analysis of variance (ANOVA). Results: Participants included 99 female nurses recruited by a convenient sampling method. Body mass index was positively and significantly related to systolic blood pressure. Waist circumference was positively and significantly correlated with systolic blood pressure and diastolic blood pressure. Conicity index was positively and significantly associated with systolic blood pressure, diastolic blood pressure, and fasting blood glucose. Age, weight and systolic blood pressure were correlated with conicity index quartiles. There was association between conicity index quartiles and waist circumference. Conclusion: The observed associations between obesity indices and cardiovascular disease risk factors suggest the importance of prevention and control of these causes of morbidity and mortality.